KALIMAT IMPERATIF DALAM FILM â€œCINDERELLAâ€ KARYA KENNETH BRANAGH (SUATU ANALISIS SINTAKSIS) - RINDORINDO, RINE SANTALIKA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABTRACT The research is entitled â€˜Imperative Sentences in the Film Cinderella by Kenneth Branagh. The objectives of this research are to identify, classify and analyze the imperative sentences. The problems of this research are focused on the forms and functions of imperative sentences. The data are taken from the Film â€˜Cinderellaâ€™ by Kenneth Branagh and the method of research is descriptive method.Â The identification and classification of the data are based on the theory of Quirk and Greenbeum related to the forms of imperative sentence. In addition, the data analysis related to the functions of imperative sentence uses the theory of Aarts and Aarts. The result of this research show that the forms consist of commands without subject (sixty nine sentences), commands with a subject (twenty eight sentences), commands with let or letâ€™s (eleven sentences), negative commands (eight sentences), and persuasive commands (six sentences). Command without subject is the most used form by the characters in film â€˜Cinderellaâ€™; In term of the function of imperative sentence, they are command, wish, invitation and warning. The most used function in the film is command. —————————————————————————————– Key words: Imperative sentence, Forms and Functions, Film â€˜Cinderellaâ€™.